Use of carbon nano tube (CNT)/ graphene oxide (GO) modified hydrogels with bacteria encapsulated for self-healing concrete - Radhiah Elyssa Rohaizat (Nanyang Technological University, 2021)
Concrete is widely used in many structures. The research on self-healing concrete has been around for many years. Its aim is to automatically repair cracks that arise in most concrete structures as a result of shrinkage, tensile forces, and other factors. However, there has yet to be an optimal self-healing technique that can be implemented and used widely in real life applications. This report aims to review the development of bacteria-based self-healing concrete and, introduce the use of nano materials to achieve optimal self-healing property. Two types of nano materials are used and examined to compare their self-healing efficiency. On top of that, two types of healing conditions are evaluated and compared to determine the best and most promising healing condition that can be applied in real engineering applications.